Cyclogenesis and mineragenic features of Early Permian sediments of the western part of Peredovoi range (North Caucasus) - A. G. Granovsky; A. N. Lednev (Известия высших учебных заведений: Геология и разведка, 2017)
Ritmostratigrafic complexes of Early Permian sediments of Belorechenskaya depression of the western part of the Peredovoy range (Front Range) have been distinguished. Single cycles of the accumulation of the red continental molasses have been established in sections of Aksautskaya and Kinyrchadskaya formations. The cyclic recurrence is associated with the differentiation of the water-flow accumulation in the intermountain trough within wandering channels and extensive debris cones in enclosed shallow basins. The sedimentation occurred in the continental environment of the intermountain accumulative plains under fluvial sedimentation conditions. It refers to the migration-mutation sedimentation type and corresponds to the upper continental molasses. Both, the mineragenic features of copper and gold in the Early Permian red sediments and the confinedness of the mineralization to the specific parts of the rock sections within the limits of the distinguished rhythms, have been shown.